Production and Post-Harvest Technologies of Small Millets for hilly areas - Sood, Salej; Atheequlla, G A; Kant, A Lakshmi; Pattanayak, A (Indian Farming, 2018)
There is need to create awareness among people about the nutritional benefits of eating small millets for popularization of these nutri-cereals. Initiative for Nutritional Security through Intensive Millet Promotion (INSIMP) programme started by Government of India in 2011 is a welcome step for promotion of nutritional benefits of these crops.